Radiographic imaging of metabolic bone disorders in consonance with biochemical parameters - Chandna, Parveen; J., Pramod Setty; M. U., Jeevika; Kochar, Praveen Kumar Tejmal; M. B., Siddesh (International Journal of Research in Medical Sciences, 2016)
Background: Bone is a strong dynamic organ of the endoskeleton playing a vital role in structural integrity envisaging keeping proper shape and maintenance of the body, mineral reservoirs, blood production, coagulation and immunity. Metabolic bone diseases are a heterogeneous group of disorders that interrupt the normal homeostasis of bone formation and resorption. Bone regulates as well as acts as a host for hematopoiesis by providing niche for proliferation and differentiation of hematopoietic cell. Bone is a dynamic tissue but metabolically active as it is being constantly formed (modelling) and reformed (remodelling). Metabolic bone diseases comprise of a broad spectrum of inherited and acquired disorders characterized by abnormalities in calcium metabolism and bone cell physiology- that lead to an altered serum calcium concentration and skeletal failure. Methods: After taking a properly informed written consent and complete history, thorough clinical examination was done and these patients were subjected to radiographic imaging and biochemical analysis. Results: With regards to fracture relating to different skeletal structures frequency was more in vertebra (38%), the maximum to be reported in 38 cases followed by hip fractures (17%) in 17 cases. Pelvis fractures were reported as (11%) in 11 cases and tibia fractures were reported to be only (7%) in meagre population of 7 cases, while remaining skeletal organs had (27%) fractures with subject to realisation in other 27 cases. Conclusions: In all the osteoporotic cases irrespective to age of patients, values of serum calcium, serum alkaline phosphatase, serum phosphorus, serum potassium, serum sodium, serum calcidiol were within normal limits.